(untitled) (Homiletic, 2019)
This article investigates how so-called “shepherds” (mpiandry) in the Malagasy revival movement (Fifohazana) recognize, identify, and address fears through their preaching in what here are called healing services. The services follow a strict liturgy and allow for homiletical spaces where fears are expressed and addressed. This essay presents a few detailed stories from field material produced from qualitative research interviews and observation of preaching in these services. The specific emphasis in the material reveals how in their preaching the shepherds interpret the problems of life in terms of a fight with evil spirits and the devil. Preaching in the movement transforms and empowers vulnerable and excluded people, it reconciles them with God, and it gives meaning and direction to their day-to-day struggles. The preaching, however, is mainly occupied with individual salvation. The author challenges the movement to find contextually and culturally coherent ways to advocate for justice for the vulnerable and excluded.